AB1013 CYCLOPHOSPHAMIDE VS AZATHIOPRINE FOR THE TREATMENT OF CONNECTIVE TISSUE RELATED INTERSTITIAL LUNG DISEASE. (2nd June 2020) - Satiş, H.; Onut, M.; Bilici Salman, R.; Babaoglu, H.; Atas, N.; Avanoğlu Güler, A.; Karadeniz, H.; Yapar, D.; Kayahan, N.; Küçük, H.; Haznedaroglu, S.; Goker, B.; et al.
Abstract : Background: Interstitial lung disease (ILD) is a common morbidity and mortalitiy reason for connective tissue disorders (CTD). Data related to treatment options in the literature is limited Objectives: To describe the role of azathiopurine (AZA) in the first line treatment of connective tissue disease related interstitial lung disease CTD-ILD, comparing with cyclophosphamide (CYC) Methods: Between 2009 and 2019 all interstitial lung disease patients admitting rheumatology or pulmonology department were retrospectively evaluated. Among those patients, as an first line regimen treated with either azathiopurine or cyclophospamide were included. Primary end point was FVC percentage change at 6th month. Results: Among 328 CTD-ILD, 57 patients had AZA treat and 79 patients had CYC for the first line treatment. Patients treated with AZA tend to have limited disease and older age. CYC treatment had a mean of 2, 41% increase in FVC but in AZA -1, 44% decrease in FVC predicted (p:0, 041) 5 major CTD groups were defined (systemic sclerosis (SSc), rheumatoid arthritis (RA), primer sjögren syndrome (pSS), dermatomyositis/ polimyositis (PM/DM), autoimmune features of intestitial lung disease (IPAF)). AZA had similar efficacy in, PM/DM and IPAF groups but worse outcome in SSc, RA and pSS compared to CYC. Conclusion: AZA treatment might be an option patients with limited disease extent and the diagnosis of PM/DM or IPAF. CYC was a better treatment in SSc, RA and pSS patients References: [1]Kocheril, S.V., et al., Comparison of disease progression and mortality of connective tissue disease-related interstitial lung disease and idiopathic interstitial pneumonia. Arthritis Care & Research: Official Journal of the American College of Rheumatology, 2005. 53 (4): p. 549-557. Disclosure of Interests: None declared